Empowering E-governance with E-voting - Amarjeet Singh; Ramakanth Kumar P; Nagaraj G Cholli (Institute of Advanced Engineering and Science, 2018)
Advances in Information and Communications Technology (ICT) have impacted the society in many ways. Be it education, healthcare, media or governance, the transformation is visible. As individual entities like education or healthcare systems have already implemented ICT to certain extent, e-governance is yet to make a significant progress even though several initiatives are undertaken. E-governance means activities like voting, administration, financial transaction etc., are enabled using automation systems. This paper discusses one part of the e-governance; e-voting. As e-voting empowers government, there are lot of challenges in implementing the e-voting system considering security threats and confidentiality involved in it. Online voting (e-voting) needs to be deployed as more convenient, relatively secure and less resource consuming system. E-voting system should ensure convenience for people to be able to access the system from personal or public computer with security and confidentiality. The presence of e-voting system with all the necessary security measures and convenience can be a potential solution for low voter turnout at the polls. The presented work demonstrates an online e-voting prototype system called SecureV. The proposed model achieves specific tasks namely, maintaining the anonymity of the voter, encryption of the vote, integrity check and avoids second time voting.